2000
DOI: 10.2165/00002018-200022020-00007
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Costs of Adverse Drug Reactions During Hospitalisation

Abstract: Computer monitoring is an effective method for improving the detection of adverse drug reactions in inpatients. The excess length of stay and costs caused by adverse drug reactions are substantial and might be considerably reduced by earlier detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(55 citation statements)
references
References 27 publications
1
52
1
1
Order By: Relevance
“…Considering the severity of the ADRs, majority were moderate similar to the results of some studies [3,5,28] but different from the results of certain other studies [36,37] in which reported ADRs were more often mild. Only a small percentage of the reactions were severe in nature.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Considering the severity of the ADRs, majority were moderate similar to the results of some studies [3,5,28] but different from the results of certain other studies [36,37] in which reported ADRs were more often mild. Only a small percentage of the reactions were severe in nature.…”
Section: Discussioncontrasting
confidence: 66%
“…ADRs are a frequent cause of hospitalization, and occur often in hospitalized patients [3][4][5][6][7]. Around 6% of hospital admissions are estimated to be due to ADRs and about 6-15% of hospitalized patients experience a serious ADR [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…(6,8) Furthermore, ADRs may occur in 6-20% of patients admitted to hospitals, increasing the hospitalization period, thus increasing the costs associated with health care. (9) ADRs have a direct impact on National Health Services (SNS) costs and even an indirect impact on patients and family in economic, social and psychological way.…”
Section: Introduction In Pharmacovigilancementioning
confidence: 99%
“…ADRs can have a significantly impact on hospitals' budget and, consequently, can lead to important charges to healthcare systems. (9) Because not all adverse drug reactions of a product are known once it's granted marketing authorization, pharmacovigilance is needed to learn more about possible harmful effects of a drug. According to WHO, (1) pharmacovigilance plays a vital role in ensuring that healthcare professionals, such as physicians and pharmacy professionals, together with the patient, have enough information to make an educated decision when it comes to choosing a drug for treatment.…”
Section: Introduction In Pharmacovigilancementioning
confidence: 99%
“…Data are usually collected by hospital pharmacies, quality improvement and risk management departments, and physician peer review systems, although underreporting is common. Medication errors and adverse drug reactions are common and costly [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%